IMPLEMENTASI PENINGKATAN KEPROFESIAN BERKELANJUTAN (PKB) DI SMKN 1 SEYEGAN SLEMAN JURUSAN TEKNIK GAMBAR - Muhammad Nuruzzaman; Sutarto HP (Universitas Negeri Yogyakarta, 2019)
ABSTRACT This study aims to: (1) know the perception of teachers of the ADT Department, SMKN 1 Seyegan of procedures and requirements of the CPD imposed by the government, (2) know the effectiveness of the CPD implementation on scientific publication aspect at the ADT Department, SMKN 1 Seyegan, and (3) know the effectiveness of the CPD implementation on innovative work aspect at the ADT Department, SMKN 1 Seyegan. This research was a descriptive research. The study population was all teachers who taught in ADT majors totalling 32 teachers (18 normative teachers, 10 adaptive teachers, and 4 productive teachers) and the whole population became the sample. The data were collected using a questionnaire and through interviews. The data analysis used the quantitative descriptive statistical technique for the quantitative data and the qualitative descriptive technique for the qualitative data. The results were as follows. (1) The perception of the teachers of Department of Architectural Drawing Technique (ADT) of SMKN 1 Seyegan Sleman toward CPD procedure was in a good category (X = 4,96, good category = 4,5 â‰¤ X <6,75). (2) The effectiveness of CPD implementation on scientific publication aspect at the ADT Department of SMKN 1 Seyegan was ineffective category (12,13%). (3) The effectiveness of CPD implementation on innovative work aspect at the ADT Department of SMKN 1 Seyegan was ineffective category (22,26%). Keywords: implementation, continuing professional development (CPD), architectural drawing technique ABSTRAK Kajian ini bertujuan untuk: (1) mengetahui persepsi guru SMKN 1 Seyegan Jurusan TGB terhadap prosedur kenaikan pangkat PKB; (2) mengetahui keefektifan implementasi PKB pada aspek publikasi ilmiah di SMKN 1 Seyegan Jurusan TGB, dan (3) mengetahui keefektifan implementasi PKB pada aspek karya inovatif di SMKN 1 Seyegan Jurusan TGB. Kajian ini merupakan Kajian diskriptif. Populasi Kajian adalah seluruh guru yang mengajar di Jurusan TGB, yang berjumlah 32 orang (18 guru normatif, 10 guru adaptif, dan 4 guru produktif) dan keseluruhan populasi dijadikan sampel. Pengumpulan data menggunakan kuesioner dan melalui wawancara. Analisis data menggunakan teknik statistik deskriptif kuantitatif untuk data kuantitatif dan teknik diskriptif kualitatif untuk data kualitatif. Hasil Kajian adalah sebagai berikut. (1) Persepsi guru SMKN 1 Seyegan Sleman Jurusan TGB terhadap prosedur kenaikan pangkat PKB masuk kategori baik (X=4,96, kategori baik=4,5 â‰¤ X < 6,75). (2) Keefektifan implementasi PKB aspek publikasi ilmiah di SMKN 1 Seyegan Jurusan TGB masuk kategori tidak efektif (12,13%). (3) Keefektifan implementasi PKB aspek karya inovatif di SMKN 1 Seyegan Jurusan TGB masuk kategori tidak efektif (22,26%). Kata Kunci: implementasi, peningkatan keprofesian berkelanjutan (PKB), teknik gambar bangunan (TGB)